(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The endometrium is a complex multicellular tissue that undergoes dynamic remodelling to establish a microenvironment that is suitable for supporting a pregnancy. Low-dose aspirin is thought to increase uterine blood flow thus improving implantation in early pregnancy.Aim: The current study aimed to estimate the role of low-dose aspirin in increasing fertility among reproductive-age women.Patients and Methods: A comparative clinical trial was conducted in Salahadeen General Hospital /Gynecology and Obstetrics department and ultrasound private clinic in Baghdad during the period from 1st of January to 30th of June 2022. A convenient sample of 100 women who were at the secretory phase of the uterine cycle and planned to become pregnant in the next cycle wasenrolled. The sample was divided into two groups: The intervention group (including 50 women who received low-dose aspirin (100 mg/day) starting on day 3 of the next ovulatory cycle beyond their enrollment in the current study) and the control group(which included 50 women without intervention)Results: According to the results of the current study, aspirin was associated with a higher percentage of trilaminar endometrial wall. Aspirin was significantly associated with increased endometrial wall thickness in the intervention group. There was a significant decrease in the resistance index after aspirin use in the intervention group, there was no significant association between aspirin use and the pulsatility index. The proportion of women who become pregnant was significantly higher in the intervention group than in the control group. In conclusion, the use of aspirin in the secretory phase in pre-implantation was associated with an increase in endometrial thickness, improvement of the endometrial pattern, decrease in the resistance index of the uterineartery, and increase in the pregnancy rate.